2008
DOI: 10.1002/hbm.20570
|View full text |Cite
|
Sign up to set email alerts
|

Automatic fMRI‐guided MEG multidipole localization for visual responses

Abstract: Previously, we introduced the use of individual cortical location and orientation constraints in the spatiotemporal Bayesian dipole analysis setting proposed by Jun et al. ([2005]; Neuroimage 28:84-98). However, the model's performance was limited by slow convergence and multimodality of the numerically estimated posterior distribution. In this paper, we present an intuitive way to exploit functional magnetic resonance imaging (fMRI) data in the Markov chain Monte Carlo sampling -based inverse estimation of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…Further, we demonstrated that this approach could reveal predictable effects of the eccentricity and size of the stimulus object on the topography of cortical currents, as illustrated with the analysis of the PROXIMATE run in this study. The correspondence with the fMRI retinotopic maps was shown in one subject (see Supplementary Material 1) and strengthens the significance of these results, even though the comparison remains qualitative at this point (Auranen et al, 2009).…”
Section: Spatial Resolution Of Msi Mapssupporting
confidence: 62%
“…Further, we demonstrated that this approach could reveal predictable effects of the eccentricity and size of the stimulus object on the topography of cortical currents, as illustrated with the analysis of the PROXIMATE run in this study. The correspondence with the fMRI retinotopic maps was shown in one subject (see Supplementary Material 1) and strengthens the significance of these results, even though the comparison remains qualitative at this point (Auranen et al, 2009).…”
Section: Spatial Resolution Of Msi Mapssupporting
confidence: 62%
“…Naturally, there are numerous open questions and alternative mechanisms that need to be addressed in future experimental work. Rapid advances in functional neuroimaging techniques in humans (Ahveninen et al, 2006; Auranen et al, 2009; Lin et al, 2006; Nummenmaa et al, 2007), as well as developments in multi-neuron recordings in animals (Ohki et al, 2005) are making it possible to study the outstanding questions in detail.…”
Section: Discussionmentioning
confidence: 99%
“…A rich literature exists that describes the correlation between neuronal oscillations as recorded by MEG and different brain functions, including attention, visual processing or motor planning (Bandettini 2009). Recently, a growing number of studies have employed both MEG and fMRI, taking advantage of the strengths of each method (i.e., excellent spatial resolution of fMRI and the millisecond temporal resolution of MEG) to help uncover the mechanisms of cortical processing (Auranen and others 2009). …”
Section: Pain Imaging: Methods 101 (Figure 3)mentioning
confidence: 99%